Pantogam activ (D-, L-hopantenic acid) in the treatment of cognitive and anxiety disorders in patients with arterial hypertension - A. B. Smulevich; B. A. Volel; E. S. Ternovaya; Yu. M. Nikitina (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева)
Objective - to evaluate the efficacy and safety of D-, L- hopantenic acid (pantogam active) on cognitive and anxiety disorders in patients with arterial hypertension. Material and methods. Autors selected 80 inpatients of a cardiology department with the verified diagnosis of hypertension and comorbid cognitive and anxiety disorders (50 patients in the main group, 30 patients in the control one). All patients received standard cardiotropic hypotensive treatment. Patients of the main group received in addition pantogam active in the daily dose from 600 to 1200 mg. Psychopathological and psychometric examinations were conducted, the data were compared with the dynamics of physical parameters (ECG, ambulatory blood pressure monitoring, blood chemistry). The duration of treatment with pantogam activ was 28 days. Results. There was a significant reduction in both cognitive and anxiety disorders in the main group compared with the controls and in patients with a history of stroke. The positive dynamics was observed during the treatment period. Conclusions. Authors support the possibility of using D-, L-hopantenic acid (pantogam active) as a drug of choice with bimodal activity (nootropic and tranquilizing) in the treatment of cognitive and anxiety disorders in patients with arterial hypertension. A rapid (in the first week) significant reduction of cognitive and anxiety disorders during the treatment with pantogam activ was noted.